2016
DOI: 10.1007/s00468-016-1402-9
|View full text |Cite
|
Sign up to set email alerts
|

Climate control on ring width and intra-annual density fluctuations in Pinus kesiya growing in a sub-tropical forest of Manipur, Northeast India

Abstract: Key message Growth ring study of Pinus kesiya (khasi pine) growing in sub-tropical forest in Manipur, northeast India was performed to understand climate signatures in ring widths and intra-annual density fluctuations. Abstract The growth rings in khasi pine (Pinus kesiya Royle ex Gordon) growing in sub-tropical Reserve Forest in Imphal, Manipur, northeast India were analysed to understand environmental signals present in ring-width series and intra-annual density fluctuations (IADFs). For this the growth ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Our results of negative correlations of diameter increment with temperature in PIKE during the dry period in the hottest months of the year are in accordance with the results from studies of the same species conducted in northwestern Thailand [51] and northeastern India [52]. The negative correlation of tree growth with precipitation during the monsoon season in August, however, is in contrast to the results obtained by Pumijumnong and Wanyaphet [53] of a positive association of P. kesiya's diameter increment with precipitation during the monsoon period in September.…”
Section: Tree Growth and Climate Signalssupporting
confidence: 91%
“…Our results of negative correlations of diameter increment with temperature in PIKE during the dry period in the hottest months of the year are in accordance with the results from studies of the same species conducted in northwestern Thailand [51] and northeastern India [52]. The negative correlation of tree growth with precipitation during the monsoon season in August, however, is in contrast to the results obtained by Pumijumnong and Wanyaphet [53] of a positive association of P. kesiya's diameter increment with precipitation during the monsoon period in September.…”
Section: Tree Growth and Climate Signalssupporting
confidence: 91%
“…This station records monthly mean temperature and total monthly precipitation for 1955-2012 C.E. This dataset has been analyzed in Singh et al (2016) and showed that the station recorded June as the wettest month with total precipitation reaching over 256 mm. The months of May to September receive over 2/3rd of the annual precipitation (1400 mm) and considered as very humid season.…”
Section: Study Sitementioning
confidence: 99%
“…For its proper growth it requires moist conditions having an annual rainfall of 200 cm with well-drained soils, while extreme heat or cold conditions have a detrimental effect on the tree (Krishnamurthi, 1969). The tree-ring studies on this species have been carried out in India (Chaudhary & Bhattacharyya, 2002;Singh & Venugopal, 2011;Shah & Bhattacharyya, 2012;Singh et al, 2016, Upadhyay et al, 2019 and Thailand (Buckley et al, 1995;Pumijumnong & Wanyaphet, 2006;Pumijumnong & Eckstein, 2011). The dendrochronological importance of this species is well established and we further make an attempt to investigate its relationship with climate variations in the Manipur region.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Singh et al (2016) are able to assign these features to short-term fluctuations in precipitation. While latewood IADFs are formed by earlywood-like tracheids with wide cell lumen formed during periods with excessive rainfall in the late growing season, earlywood IADFs are triggered by deficient moisture availability during the early growing season around May, after tree growth has been activated by precipitation in the pre-monsoon season in April.…”
mentioning
confidence: 99%